A survey of testicular texture in canine ultrasound images - McEvoy, Fintan J.; Pongvittayanon, Panida; Vedel, Tanja; Holst, Pernille; Müller, Anna V. (Frontiers in Veterinary Science, 2023)
Computer-based texture analysis provides objective data that can be extracted from medical images, including ultrasound images. One popular methodology involves the generation of a grey-level co-occurrence matrix (GLCM) from the image and from that matrix, texture fractures can be extracted. We performed such analysis on 280 ultrasound testicular images obtained from 70 dogs and explored the resulting texture data, by means of principal component analysis (PCA). Various abnormal lesions were identified subjectively in 35 of the 280 cropped images. In 16 images, pinpoint-to-small, well-defined, hyperechoic foci were identified without acoustic shadowing. These latter images were classified as having ``microliths". The remaining 19 images with other lesions and areas of non-homogeneous testicular parenchyma were as classified ``other". In the PCA scores plot, most of the images with lesions were clustered. These clustered images represented by those scores had higher values for the texture features entropy, dissimilarity, and contrast, and lower values for angular second moment and energy in the first principal component. Other data relating to the dogs, including age and history of treatment for prostatomegaly or chemical castration did not show clustering on the PCA. This study illustrates that objective texture analysis in testicular ultrasound correlates to some of the visual features used in subjective interpretation and provides quantitative data for parameters that are highly subjective by human observer analysis. The study demonstrated a potential for texture analysis in prediction models in dogs with testicular abnormalities.